ByzRev 06.2024.034: Giedré Mickunaite, Maniera Greca in Europe’s Catholic East.: On Identities of Images in Lithuania and Poland, 1380s–1720s (Central European Medieval Studies 6). Amsterdam: Amsterdam University Press 2023. - Kruk, Mirosław Piotr (The Byzantine Review, 2024)
Giedré Mickunaite, Maniera Greca in Europe’s Catholic East. On Identities of Images in Lithuania and Poland, 1380s–1720s (Central European Medieval Studies 6). Amsterdam: Amsterdam University Press 2023. 238 pp. – ISBN 978-90-485-3270-4